A Comparative Study of the Mechanical Properties of Basalt Fiber and Basalt Grille Reinforced Concrete Composites and Theoretical Prediction. Issue 13 (1st December 2022) - Jia, Minghao; Xie, Wanzi; Yu, Kejing; Qian, Kun
ABSTRACT: In this study, the chopped basalt fiber (CBF) with different content and basalt fiber grilles (BFG) with different layers were composed with concrete matrix, respectively. The compressive, splitting tensile and flexural properties of concrete composites were studied by universal material testing machine. The cracks evolution law of specimens was analyzed to reveal the reinforcement mechanism of CBF and BFG. Results showed that under the same fiber volume ratio, BFG were better than CBF to reinforce mechanical properties of concrete. The three kinds of mechanical properties of BFG reinforced concrete were improved highest by 41.46%, 28.26% and 46.13%, respectively. BFG can play a crucial role in stress transmission, bearing load and absorbing energy during the loading process of the specimens. Based on the equivalent stress rectangle theory, an analytic model to predict the ultimate flexural capacity of BFG reinforced concrete was proposed. The experimental results from the flexural test were compared with the predicted values, and a good accuracy of the analytic model was obtained.